Bit Error Performance of APD and SPAD Receivers in Optical Wireless Communication - Hiwa Mahmoudi (MDPI AG, 2021)
This review concentrates on the state-of-the-art hardware-oriented receiver aspects for optical wireless communication (OWC), and points to the importance of BER performance analysis and modeling in presence of non-perpendicular light incidence. Receivers in OWC networks for 6G applications have to work for strongly different light incidence angles, to allow the formation of connections to locally separated transceivers without the need for rotation units and accurate adjustment. In turn, and in combination with fully integrated optical receivers, reduction of cost and increased comfort can be achieved. Fully integrated [bipolar] complementary metal-oxide-semiconductor ([Bi]CMOS) receivers with on-chip avalanche photodiodes (APDs) and single-photon avalanche diodes (SPADs) are presented and their performance in optical wireless communication is summarized. Impressive data rates up to 2 Gbit/s and free-space transmission distances up to 27 m at bit error ratios (BER) below 10−9 are reached with linear-mode APD receivers. The importance of optical interference in the isolation and passivation stack on top of the integrated photodiodes is illuminated. To be able to predict the dependence of the BER of single-photon avalanche diode (SPAD) receivers on the light incidence angle, a model, which includes a model for the photon detection probability and a standing-wave model for the isolation and passivation stack, is extended. The dependence of the BER on the light incidence angle onto the photodiodes is investigated by electromagnetic simulation for optical transmission of the layers on top of the photodiode, device simulation for the avalanche triggering probability and BER modeling with MATLAB. It is found that incidence angles up to 30° have moderate influence on the BER and that the BER degrades significantly for incidence angles larger than 50°.